When hoofbeats mean zebras not horses: Tumour mimics of subdural haematoma – Case series and literature review. (September 2019) - Tan, Leanne Qiaojing; Loh, Daniel De-Liang; Qiu, Liming; Ng, Yew Poh; Hwang, Peter Ying Khai
Highlights: Case reports of 3 different tumour mimics of chronic subdural haematoma. Review of previous similar case studies or series. Proposed decision algorithm for further investigation for suspicious SDH mimics. Abstract: Chronic subdural haematomas are common neurosurgical conditions, especially in the elderly patients, with straightforward surgical treatments. However, infrequently, tumours are misdiagnosed as subdural haematoma on initial brain CT scans and are only discovered intraoperatively. In this case series, we presented 3 different patients who were initially thought to have subdural haematoma but later found to be tumour mimics of different histological origin. A literature review and discussion of recently published tumour mimics of subdural haematoma was also performed. It is recommended that in patients with suggestive oncological or haematological history, or unusual characteristics on the plain CT brain, a high level of suspicion of tumour mimics needs to be maintained. A full workup with contrast-enhanced magnetic resonance imaging is important to distinguish from subdural haematoma, as the treatment paradigms and prognoses are vastly different.